Enhancement and isolation of zerumbone in Zingiber zerumbet (L.) Smith cell suspension and adventitious root cultures / Mahanom Jalil - Mahanom , Jalil (2018)
Zingiber zerumbet Smith is a highly valuable medicinal ginger belonging to Zingiberaceae family containing bioactive phytomedicinal compound called zerumbone (ZER). Limitation in Zingiberaceae conventional breeding techniques makes alternative approach through biotechnological plant tissue culture as the most practical route to obtain targeted bioactive compound(s). In this study, production of ZER was carried out using two in vitro culture systems namely cell suspension and adventitious roots. The establishment of cell suspension culture under selected set of physiochemical parameters was investigated for biomass growth and ZER production. It was found that the type of carbohydrate substrate, light regime, agitation speed, and incubation temperature showed significant effects on the production of ZER. The highest specific growth rate of cells was recorded in liquid Murashige and Skoog (MS) basal medium containing 3% sucrose with pH 5.7 and incubated under continuous shaking of 70 rpm with 16 hr photoperiod at 24°C. However, the yield of ZER in cell suspension cultures of Z. zerumbet was low and extracellular, thus making the compound enhancement and recovery complicated. Consequently, development and optimization of Z. zerumbet adventitious root (AdR) culture was carried out. From the results, the frequency of root response, number of roots per explant, root length, and ZER production were affected by the concentration and types of auxins used for both AdR initiated through direct and indirect organogenesis (AdRD and AdRId respectively). For roots multiplication, the highest specific growth rate was achieved in AdRId with an initial inoculum of 0.5 g fresh weight (FW) in full strength MS medium. Nevertheless, the amount of ZER was found to be highest in half strength MS in AdRD at 2520 μg g-1 DW (p0.05). In order to enhance ZER production, elicitation strategy was employed on selected root cultures. It was observed that salicylic acid (SA) was more efficient at lower concentration compared to methyl jasmonate (MeJA) in eliciting ZER secretion by the root culture. In contrast, the biomass harvested from SA-treated root culture was significantly lower to MeJA-treated culture, hence demanding longer period of cultivation prior to harvesting. Therefore, further optimization was carried out based on the time interval for supplementation of optimized MeJA concentration (800 μM) at 15, 20 and 25 days of cultivation. MeJA treatment during exponential phase (supplementation at day 15) significantly increased ZER expression at 42,777 μgg-1 DW (p0.05). The yield obtained was comparable to the ZER extracted from field-grown rhizome. Elicitor treatment to plant cell cultures whilst enhanced the production of secondary metabolite, it also induced oxidative stress, indicated by the increase in intracellular concentration of hydrogen peroxide (H2O2). Thus, the relationship between ZER production and the profiles of hydrogen peroxide (H2O2) concentration, catalase (CAT) and ascorbate peroxidase (APX) activities were investigated for untreated (control) and MeJA elicited roots. However, conclusive pattern relating the variables studied in the untreated control culture was absent. In elicited roots, the concentration of H2O2 was found to be significantly high, which was attributed to the oxidative stress response from elicitor addition. Since large-scale production is necessary for compound harvesting, the AdR of Z. zerumbet was propagated in a controlled balloon-type column bioreactor (BTBCB). From the results, volume of initial inoculum and aeration rate affected the specific growth rate and ZER production while pH affected the root biomass growth but showed no significant effect on ZER accumulation. Lower initial inoculum density (10 gL-1) yielded the highest specific growth rate while ZER production was highest when initial inoculum density was 20 gL-1. Optimum aeration rate at 1.0 Lmin-1 resulted in a three-fold increment of initial biomass and highest ZER accumulation. In conclusion, AdR system with elicitation strategies showed promising results in ZER production from Z. zerumbet root cultures, and this could be applied as a model system for large-scale production of similar plant metabolites.